Total Sulfated Glycosaminoglycan (GAG) From Malaysian Sea Cucumbers Stichopus Hermanni And Stichopus Vastus And Its Effects On Wound Healing In Rats - Masre, Siti Fathiah (2011)
Sea cucumbers have long been exploited as a source of medicinal compounds due to the presence of sulfated glycosaminoglycans (GAGs). The aim of this study was to investigate the occurrence of total sulfated GAG from the integument body wall, the visceral internal organs and the coelomic fluid of Malaysian sea cucumbers Stichopus hermanni and Stichopus vastus and evaluate the effect of total sulfated GAG on wound healing in rats using macroscopic and microscopic evaluations.